Effect of Hydrogen on Cracking Reaction Products 9-Octadecenoate (Aleic Acid) Into Alkane Short Fraction Compounds - Donatus Setyawan Purwo Handoko; Triyono (Formosa Journal of Sustainable Research, 2023)
Research has been carried out on the effect of hydrogen on the cracking of 9-octadenoate into short fraction compounds. The research was conducted at the UGM physical chemistry laboratory with Prof. Dr. Triyono, MS. The research implementation that must be prepared first is the Ni/Zeolite catalyst. Ni/Zeolite catalyst preparation was carried out by immersing 500 grams of zeolite in H2O for 24 hours while stirring. Then proceed with calcination with nitrogen gas for 3 hours at a nitrogen gas flow rate of 2.5 mL/minute. After that it was cooled and continued with oxidation with oxygen gas flowing at a rate of 2.5 mL/minute for 3 hours. Then after that, cooling was carried out and then followed by acid treatment through a reflux process with 4 Molar HCl for 3 hours and every 1 hour replaced with the same solution. After that, it was followed by reflux treatment with 1M NH4Cl for 1 hour, after that it was cooled and filtered, then the oxidation process was carried out with oxygen gas for 3 hours, with an oxygen flow rate of 2.5 mL/minute. Then proceed with reduction with hydrogen gas for 3 hours at a flow rate of 2.5 mL/minute after that the catalyst is cooled. After cold, impregnation was carried out with metal Ni(NO3)2.9H2O, after impregnation a reduction process was carried out with hydrogen gas for 3 hours at a flow rate of 2.5 mL/minute, so that a Ni/zeolite catalyst was obtained